Treatment of a patient with tooth 2.1 chronic apical periodontitis in the presence of tooth 2.2 root perforation. Clinical case (Эндодонтия Today)
Perforation of hard tooth tissues is one of the most common complications of endodontic treatment. According to statistics, perforations account for 9% of the total number of complications in endodontics. The frequently asked question about the preservation or removal of a tooth with a perforation – is a question of a correctly accepted decision with a deep clinical situation analysis and a correctly chosen treatment tactic. On the example of endodontic retreatment of tooth 2.1 chronic apical periodontitis and tooth 2.2 perforation in the middle third of the root, the article details the complications reasons in endodontics, stage-by-stage treatment, results are presented in detail, as well as a number of 3D CT-images confirming the rationality of the chosen tactics.